PROGRAM PENINGKATAN KOMPETENSI AUDIT MELALUI PELATIHAN PENYUSUNAN WORKING PAPER BAGI MAHASISWA MAGANG DI KANTOR AKUNTAN PUBLIK - Wan Fachruddin; Haflah Furqan (Jurnal Pengabdian Bukit Pengharapan, 2026)
Kampus Berdampak Program, part of the Merdeka Belajar Kampus Merdeka policy, provides opportunities for university students to develop professional competencies through internship activities in the workplace. This article documents a community service program implemented through an internship by three students of the Accounting Study Program at Universitas Pembangunan Panca Budi at the Public Accounting Firm Gideon Adi dan Rekan. The primary objective of the activity was to enhance audit competencies, particularly the ability to prepare audit working papers in a correct, well-documented manner that conforms to the Indonesian Professional Accountant Standards and International Standard on Auditing 230. The implementation method was a PKM Socialization program combining three elements: direction and direct demonstration from the UNPAB field supervisor lecturer on how to prepare proper working papers in an audit, mentoring by the partner namely a senior auditor at the Public Accounting Firm Gideon Adi dan Rekan, and student involvement in real audit assignments. The evaluation was entirely process-based through work observation by the partner and lecturer, review of working paper portfolios, and reflection on internship experiences. Results showed that the three students acquired knowledge about audit documentation regulations, working paper structure, and the principles of SPAP and ISA 230, while simultaneously gaining technical audit skills such as vouching, tracing, verification, and the preparation of current files and permanent files. The activity recommends replicating the model in other partner public accounting firms with strengthened coordination between higher education institutions and public accounting firms.